2014
DOI: 10.1021/es5015407
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Reactions of Particulate Matter-Bound PAHs and NPAHs with NO3/N2O5, OH Radicals, and O3 under Simulated Long-Range Atmospheric Transport Conditions: Reactivity and Mutagenicity

Abstract: The heterogeneous reactions of ambient particulate matter (PM)-bound polycyclic aromatic hydrocarbons (PAHs) and nitro-PAHs (NPAHs) with NO3/N2O5, OH radicals, and O3 were studied in a laboratory photochemical chamber. Ambient PM2.5 and PM10 samples were collected from Beijing, China and Riverside, California, and exposed under simulated atmospheric long-range transport conditions for O3 and OH and NO3 radicals. Changes in the masses of 23 PAHs and 20 NPAHs, as well as the direct and indirect-acting mutagenici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(66 citation statements)
references
References 60 publications
(181 reference statements)
2
64
0
Order By: Relevance
“…completely (18). Other measurements have demonstrated that heterogeneous oxidation of particle-surface-bound PAHs in the atmosphere decreases substantially due to accumulation of SOA species over particles during their atmospheric transport and chemical aging (23). Heterogeneous reactions of PAHs with ozone are limited mostly to the particle surface, where ozone can be catalytically destroyed (24).…”
mentioning
confidence: 99%
“…completely (18). Other measurements have demonstrated that heterogeneous oxidation of particle-surface-bound PAHs in the atmosphere decreases substantially due to accumulation of SOA species over particles during their atmospheric transport and chemical aging (23). Heterogeneous reactions of PAHs with ozone are limited mostly to the particle surface, where ozone can be catalytically destroyed (24).…”
mentioning
confidence: 99%
“…Although it has been shown that O 3 was an effective oxidant for heterogeneous reactions of particle-bound PACs (Jariyasopit et al, 2014), it should also be noted that in a real world environment the coexistence of O 3 and other atmospheric oxidants (e.g. OH radicals, NO 3 radicals, NO 2 , N 2 O 5 ) could complicate the degradation reactions of the PACs associated with PUF disks.…”
Section: Discussionmentioning
confidence: 99%
“…In the real environment, PACs with more than 4 rings, including reactive BaP, PER, and DahA, are mainly associated with particulate matter (Su et al, 2006;Yamasaki et al, 1982) and hence suffer from O 3 degradation to a lesser extent as they are partially shielded from gaseous oxidants by black carbon, organic matter, and the accumulation of atmospheric reaction products on the surface. (Jariyasopit et al, 2014;Lammel et al, 2009;Zhou et al, 2012) Furthermore, it is Fig. 2.…”
Section: And Si2 Supportingmentioning
confidence: 96%
See 2 more Smart Citations